2016
DOI: 10.1177/0733464815624151
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Acceptance of Activity Trackers

Abstract: Objective To assess the usability and acceptance of activity tracking technologies by older adults. Method First in our multi-method approach, we conducted heuristic evaluations of two activity trackers that revealed potential usability barriers to acceptance. Next, questionnaires and interviews were administered to 16 older adults (Mage=70, SDage=3.09, rangeage= 65-75) before and after a 28-day field study to understand facilitators and additional barriers to acceptance. These measurements were supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 27 publications
3
95
0
3
Order By: Relevance
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) and Technology Acceptance Model (TAM) provide insights into experience level influences and facilitators and barriers to the use of wearables in this study. Two important factors for user acceptance of technology are perceived ease of use (PEOU) and perceived usefulness (PU) (Davis et al 1989;Preusse et al 2016;Ma et al 2017;Venkatesh et al 2012). Perusse et al 's (2016) research found that lower PEOU and PU decreased the acceptance rate of wearables.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) and Technology Acceptance Model (TAM) provide insights into experience level influences and facilitators and barriers to the use of wearables in this study. Two important factors for user acceptance of technology are perceived ease of use (PEOU) and perceived usefulness (PU) (Davis et al 1989;Preusse et al 2016;Ma et al 2017;Venkatesh et al 2012). Perusse et al 's (2016) research found that lower PEOU and PU decreased the acceptance rate of wearables.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Perusse et al 's (2016) research found that lower PEOU and PU decreased the acceptance rate of wearables. Other problems and barriers to the use of wearable technology include weakness/lack of durability (Paul et al 2014;Wang et al 2016a, b), discomfort (Bowman et al 2016), invasive monitoring (Coorevits and Coenen 2016), inaccuracy (Kim et al 2007;Preusse et al 2016); limited designs (Colgan et al 2016;Tomberg et al 2015;Wang et al 2016a, b), cost (Donkin 2016), uselessness (Donkin 2016;Motti and Caine 2016) and difficulty of use (Coorevits and Coenen 2016). Researchers have endeavored to develop durable products that can withstand frequent washing or long-term use through methods such as coating the surface of the conductive materials or applying nanotechnologies (Paul et al 2014;Wang et al 2016a, b).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 3 more Smart Citations